Edgenta UEMS Sdn Bhd / Muhammad Naa'im Mohd Nasir - Mohd Nasir, Muhammad Naa'im (Universiti Teknologi MARA, Perlis, 2023)
My name is Muhammad Naa’im bin Mohd Nasir, a final year student majoring in Business Administration (Hons) Human Resource Management from Universiti Teknologi MARA Perlis Branch. My decision to return to Kuala Lumpur and complete my industrial training there resulted from the city's abundant supply of chances for internships, which motivated me to do so since I wanted to improve both my capabilities and my skills. As a student interested in learning more about human resource management, I decided to join the Human Resources Department to comprehensively understand everything a recent graduate must do to succeed in the current market.)